Formation of competitive advantages of enterprises in terms of globalization: competitive dynamics and an intellectual component - Tarasenko, O. S.; Тарасенко, О. С.; Yermakov, Yu. O.; Єрмаков, Ю. О.; Pchelin, V. B.; Пчелін, В. Б.; ResearcherID: L-2114-2016; Віталій Пчелін (Baltic Journal of Economic Studies. - 2017. - Vol. 3, №. 5. - P. 469-473, 2017)
Метою статті є вивчення сучасного стану наукової думки щодо формування інтелектуального капіталу підприємства в інноваційному процесі, досягнення підприємством відповідних конкурентних переваг та їх захисту. Стаття досліджує, описує і, відповідно, формалізує сучасні процеси формування конкурентних переваг в умовах інтелектуальної економіки: управління знаннями, їх патентування, сучасне значення та вплив патентування на роль інтелектуальної власності в досліджуваних явищах, а також управління відповідними інформаційними потоками. Робота одночасно синтезує важливі аспекти управління інформаційним потоком, формування інтелектуального капіталу та захист інтелектуальної власності в процесі комерціалізації результатів інноваційної діяльності.

The purpose of the article is to investigate the current state of scientific thought in relation to the formation of intellectual capital of an enterprise in the innovation process, achievement by the enterprise of corresponding competitive advantages and their protection. Methodology. The methodological basis of the article is the systematic approach, which provided a comprehensive definition of the scope of this research – intellectual property and its protection as a complex economic and legal category. This made it possible to systematically define the purpose, level of abstraction, hierarchy, forms of manifestation, and key attributes of the subject of research. Application of principles of modelling of business processes also allowed studying the influence of factors of the external environment on the sequence of information flows in the process of forming competitive advantages on the basis of intellectual property. In addition, having determined the scientific basis, the collective and local monographic studies of leading scientists concerning the specificity of the formation of competitive advantages of innovative enterprises, including on the basis of intellectual capital, were also taken into account. Results. The article studies, describes and, correspondingly, formalizes modern processes of formation of competitive advantages in the conditions of Smart Economy: knowledge management, their patenting, modern significance, and the influence of patenting on the role of intellectual property in the investigated phenomena, as well as management of relevant information flows. Practical implications. The research demonstrates ways of forming competitive advantages in the modern economy, and the results of the analysis of relevant statistics explain patterns of economic and legal processes in the field of relevant practical activities. This allows assessing the actual state of the subject of the research, determining the development trajectory, and effectively forming methods and tools for managing the relevant processes. Value/originality. The proposed approach allows ensuring the principle of unity in the research of economic and legal processes in the field of innovation activity management. The work simultaneously synthesizes important aspects of information flow management, intellectual capital formation, and intellectual property protection in the process of commercialization of results of innovation activities.

Целью статьи является изучение современного состояния научной мысли по формированию интеллектуального капитала предприятия в инновационном процессе, достижения предприятием соответствующих конкурентных преимуществ и их защиты. Статья исследует, описывает и, соответственно, формализует современные процессы формирования конкурентных преимуществ в условиях интеллектуальной экономики: управление знаниями, их патентования, современное значение и влияние патентования на роль интеллектуальной собственности в изучаемых явлениях, а также управление соответствующими информационными потоками. Работа одновременно синтезирует важные аспекты управления информационным потоком, формирование интеллектуального капитала и защиту интеллектуальной собственности в процессе коммерциализации результатов инновационной деятельности.
Keywords: Економіка. Економічний аналіз. Economy. Economic Analysis. Экономика. Экономический анализ; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; publikatsii u zarubizhnomu vydanni; publikatsii u WoS; Цивільне право. Civil Law. Гражданское право; Право інтелектуальної власності. Intellectual property law. Право интеллектуальной собственности; глобалізація; інтелектуальна економіка; конкурентна перевага; конкурентоспроможність; інтелектуальна власність; патент; глобализация; интеллектуальная экономика; конкурентное преимущество; конкурентоспособность; интеллектуальная собственность; globalization; intellectual economy; competitive advantage; competitiveness; intellectual property; patent